2008
DOI: 10.1016/j.immuni.2008.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The Balance between T Cell Receptor Signaling and Degradation at the Center of the Immunological Synapse Is Determined by Antigen Quality

Abstract: Summary The role of the immune synapse, and in particular the role of the central region of the synapse (the central supramolecular activation cluster or cSMAC), is controversial. One model suggests that the sole function of the cSMAC is to downregulate receptors and turn off signaling and that TCR signaling occurs only in the pSMAC. A second model suggests that the role of the cSMAC depends on antigen quality and can both enhance signaling and receptor downregulation. Here, we provide evidence that while at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 45 publications
2
130
0
Order By: Relevance
“…Microclusters play a predominant role in the generation of sustained signals. Current models also indicate that cluster centralization plays an important role in signal termination and that the cSMAC is a site both for TCR down-regulation yet also for amplification of weak signals (Lee et al 2003;Mossman et al 2005;Varma et al 2006;Balagopalan et al 2007;Cemerski et al 2008;Nguyen et al 2008). A recent study using a photoactivatable agonist in a lipid bilayer system has provided even greater precision in the temporal resolution of these events and demonstrated that adapters are recruited to microclusters within four seconds (Huse et al 2007).…”
Section: Lat Microclusters: Sites Of Nucleation Of Signaling Complexesmentioning
confidence: 99%
“…Microclusters play a predominant role in the generation of sustained signals. Current models also indicate that cluster centralization plays an important role in signal termination and that the cSMAC is a site both for TCR down-regulation yet also for amplification of weak signals (Lee et al 2003;Mossman et al 2005;Varma et al 2006;Balagopalan et al 2007;Cemerski et al 2008;Nguyen et al 2008). A recent study using a photoactivatable agonist in a lipid bilayer system has provided even greater precision in the temporal resolution of these events and demonstrated that adapters are recruited to microclusters within four seconds (Huse et al 2007).…”
Section: Lat Microclusters: Sites Of Nucleation Of Signaling Complexesmentioning
confidence: 99%
“…The protein patterns are not static on the cell surface 18,19 . Instead, they evolve on the timescale of signalling, usually over the course of minutes, and can change depending on the cell signalling state 15,16 . Here, we highlight recent evidence suggesting that the spatial organization of proteins at cell-cell interfaces may be a widespread regulatory mechanism of intercellular signal transduction.…”
Section: Hhmi Author Manuscriptmentioning
confidence: 99%
“…For example, this can result in location-specific signalling of identical receptors. Recent evidence suggests that the spatial organization of the immunological synapse has an active role in regulating the signalling state of individual molecular components, and thus can alter long-term cell activation [15][16][17] . Various different spatial arrangements can occur between different types of immune cells and their respective targets, correlating with different functions 8,13 .…”
mentioning
confidence: 99%
“…41 Experiments were also conducted to determine the ability of specific APLs to induce positive selection of CD4 lineage transgenic T cells. For a pigeon cytochrome C (PCC) [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] peptidespecific TCR, injections of agonist peptide alone or a mixture of antagonist and agonist peptides were given to Ii, H-2M double KO mice. 42 When injected alone, agonist peptide presumably repopulated MHC molecules in the thymus and supported positive selection of the transgenic T cells that continued for up to 2 weeks.…”
Section: Repertoires For Positive Selection Of Mhc2 Restricted Tcrsmentioning
confidence: 99%
“…53,54 Signaling molecules and kinases, such as Lck, Zap-70, LAT, SLP-76, 50,52,54 and Grb2, 55 are localized to TCR microclusters, which translocate from the periphery of the synapse to the center in an actin dependent manner where signaling is terminated, 51 although the precise function of the cSMAC remains unresolved. 56 TCR microclusters form continuously, thus providing a signaling microclusters containing TCR, CD4 and CD8 that may recognize many self-peptide-MHC complexes. This promiscuous signal transduction would be amplified by the reduction in phosphatase activity in DP thymocytes described previously.…”
Section: Tcr Microclustersmentioning
confidence: 99%